Implementation of Police Protocol Dankorbrimob Number: Protap/01/VII/2017 Concerning Operational Guidelines for the Anti-Anarchist Unit of the Police Brigade Corps (Brimob) at Satbrimob Police Metro Jaya - Tamba, Kristo; Afianto, Rangga; Haryanto, Haryanto; Tambunan, Daniel Artasasta (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to find out the implementation of Protap Dankorbrimob POLRI Number: Protap 01/VII/2017 at Satbrimob Polda Metro Jaya and to find out the factors that influence the implementation of the policy. This research uses a qualitative descriptive method, whose data collection is done through interviews, observation and documentation. The research data was analyzed using an interactive model analysis, which consists of data reduction, data presentation and conclusion drawing. The results showed that there has been an effort from Satbrimob Polda Metro Jaya to implement Protap Dankorbrimob POLRI Number: Protap/01/VII/2017 in carrying out the duties of the Anti-Anarchist Unit. However, so far, the implementation has not run optimally, as seen from the existence of several things that deviate from the provisions of the Protap, such as the minimum number of members deployed, the prohibition of the use of firearms, and formations that are never fully implemented. As for the factors that influence the implementation of the Protap, according to the implementation model from Edward III, all of them have not gone well. Communication, resources, disposition, and bureaucratic structure are all still obstacles in the implementation of Dankorbrimob POLRI Protap Number: Protap/01/VII/2017 at Satbrimob Polda Metro Jaya, which results in not optimal implementation of the policy.